Pengaruh Penggunaan Bioaktivator Lokal Terhadap Kandunag Serat Kasar, Lemak Kasar dan BETN Pelepah Sawit - tri astuti; Harissatria Harissatria; D. Hanum Putri (Jurnal Peternakan Mahaputra, 2022)
This study aims to evaluate the effect of using local bioactivators rumen contents consisting of local microorganism extract and crude enzymes on crude fiber, crude fat and The Extract matter without nitrogen content of palm fronds. The research was conducted by an experimental method using factorial design in RAL with 2 X 3 and 3 replications for each treatment. Factor A is a type of local bioactivator consisting of A1 = MOL, A2 = crude enzyme. Factor B is the dose of bioactivator, B1 = 10%, B2 = 20%, B3 = 30%. The results showed that there was no interaction between the dose and type of bioactivator on the content of crude fiber, crude fat and Extract matter without nitrogen of palm fronds.